The pantheism in Johann Wolfgang von Goethe's studies of nature - Alvarado, Arturo Rojas (2024)
This article studies the philosophical thought of Johann Wolfgang von Goethe, inside his ontological conception from his pantheism and his studies of nature, identifying the elements where both are related.